Systemic hypereosinophilic syndromes: when autoimmunity is Th2 mediated. Issue 2 (April 2020) - Matucci, Andrea; Nencini, Francesca; Maggi, Enrico; Vultaggio, Alessandra
Abstract : Purpose of review: Clinical conditions associated with hypereosinophilia represent a field of particular interest, taking into account the epidemiological impact of the different primary and secondary forms. In addition to a classical Th1 response, also Th2 cells can be involved in the pathogenesis of autoimmune diseases, among them eosinophilic forms such as eosinophilic granulomatosis with polyangiitis. Recent findings: In patients with severe asthma, recent evidence highlights the role of pathogenic autoantibodies against autologous eosinophil proteins (e.g. eosinophil peroxidase) suggest the role of autoimmune mechanisms, particularly in patients in which asthma is included in eosinophilic vasculitis with antineutrophilic autoantibody positivity. Is now evident that in addition to Th2 cells, also type 2 innate lymphoid cells and Th1/Th17 cells play a central role in the pathogenesis of hypereosinophilic syndrome. Summary: The definition of cellular and molecular mechanisms and the critical role of specific cytokines involved in the pathogenesis of hypereosinophilic syndrome open the way to new therapeutic strategies by using biological agents targeting these specific factors.